APLIKASI ALGORITMA DES (DATA ENCRYPTION STANDARD) UNTUK PENGAMAN DATA - Gunawan Putrodjojo; Julhan H. Purba; Junawano Candra (CCIT Journal, 2017)
Cryptography is a field of knowledge which uses a mathematical equation to perform the encryption and decryption process. This technique is used to convert the data into a specific code, with the aim that the stored information can not be read by anyone except those who are eligible. In this final project will be presented the design of cryptographic applications with cryptographic algorithm Data Encryption Standard. This cryptographic applications implementing encryption and decryption method using the DES algorithm.This research will presenting application design of crioptographic and its algorithm data of DES. This application will implementing the way of encryption and decription using DES. DES algorithm is adopted as standard algorithm. Since that, DES has been used in desimination information widely to protect data savely. In every day live, DES is using in many applications like to encrypt PIN (Personal Identity Number) in ATM and Banking transactions via internet. Even government organitations in US like Departmen of Energy, Justice Department, and Federal Reserve System are using DES to protect their data desiminations. The principt of DES working is devides information in special blocks, so that DES is known as cipherblock. The messages will be randomly using standard matrix in DES alhgorithm. The first proces will generate DES key algorithm. Cipherblock with 64 bits block size. Because in this application we have designed internal key altogether in enription process. The next we will to do enription process. The steps in doine encryption will begin with choosing file .txt. This file contents will be changed as binery numbers using ASCII as reference. The changing file as binary will be devided into 64 bits. Its means automatically that in DES algorithm using 8-characters or 64-bits. Next step, the deviding text will be permutated using first permutation matrix, the goal is to randomice plaintext. The randomice text will devivided into 2 blocks which 32-bits in length. Each block will use L0 dan R0 as symbol. The next process will do 16-cycling process. After 16-cycling process, both blocks will put in unity. After that, we will final permutation with using permutation matrix iP-1